2008
DOI: 10.1007/s10433-008-0084-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of increased exercise on quality of life in older adults: the UQQoL, a new instrument

Abstract: The University of Queensland Quality of Life instrument (UQQoL) was developed to provide a quantitative measure sensitive to the impact of increased exercise on the quality of life (QoL) of older individuals. This paper describes the development and testing of the UQQoL including an exploratory study of focus group interviews with 18 participants aged 65 and over, item development and selection, and instrument piloting with groups of older adults undergoing high-intensity training. The SF-36, another establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…A perfect correlation (r = 1) was found between the total score and mean score. The UQQoL has demonstrated acceptable internal consistency (α = .72; Henwood & Bartlett, 2008). In the present study, the scale demonstrated good internal consistency (α = .80).…”
Section: Satisfaction With Life Scale (Swls; Diener Emmons Larsen supporting
confidence: 54%
See 2 more Smart Citations
“…A perfect correlation (r = 1) was found between the total score and mean score. The UQQoL has demonstrated acceptable internal consistency (α = .72; Henwood & Bartlett, 2008). In the present study, the scale demonstrated good internal consistency (α = .80).…”
Section: Satisfaction With Life Scale (Swls; Diener Emmons Larsen supporting
confidence: 54%
“…The scale has also shown good convergent validity when compared with another well-validated measure of health related quality of life, the Medical Outcome Survey Short Form (MOS SF-36; Ware & Sherbourne, 1992). Specifically, the UQQoL summary score was found to correlate strongly with domains of the MOS SF-36 reflecting physical and functional health (Henwood & Bartlett, 2008). Moreover, while the MOS SF-36 can be problematic because of frequent ceiling effects, the UQQoL summary scale was found to be "well within an acceptable floor and ceiling range" (Henwood & Bartlett, 2008, p. 246).…”
Section: Satisfaction With Life Scale (Swls; Diener Emmons Larsen mentioning
confidence: 92%
See 1 more Smart Citation
“…General quality of life tools include items related to physical activity, but also include disease or general health-related items that may selectively affect clinical populations experiencing physical and social difficulties due to disease states. In fact, in at least one study the SF-36 has been found to lack sensitivity to exercise-related changes in quality of life (Henwood & Bartlett, 2008). By comparison, the VPS contains only questions related to the benefits of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the majority of adults 65 years and older with OA typically have not met the public health recommendations for type, quantity and quality of physical activity (Fontaine, Heo, & Bathon, 2004). These lower levels of physical activity are associated with a loss of muscular strength, endurance, and balance, which together contributes to an increased risk of falls and lower perceived quality of life (Henwood & Bartlett, 2008). Consequently, older adults with OA are particularly susceptible to greater than age-related reductions in muscle strength, functional ability, balance, increased rates of co-morbidities and associated declines in independence and perceived quality of life.…”
mentioning
confidence: 99%